Bisphosphonates and Age-Related Macular Degeneration: A Propensity-Matched Cohort and Nested Case-Control Analysis - Garriga, C; Judge, A; Hawley, S; Delmestri, A; Prieto-Alhambra, D; Cooper, C; Pazianas, M (American Society for Bone and Mineral Research, 2017)
Objective: To investigate the association between oral bisphosphonate (BP) use and the risk of developing age-related macular degeneration (AMD).